ANALISIS PENGARUH RETURN ON ASSET (ROA), RETURN ON EQUITY (ROE), DAN DEBT TO EQUITY RATIO (DER) TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BEI TAHUN 2020 – 2024 - Gabriella Magdalena; Sulastiningsih (Jurnal Akuntansi dan Bisnis, 2026)
Results of quantitative causal analysis of the impact of Return On Assets (ROA), Return On Equity (ROE), dan Debt to Equity Ratio (DER) on the value of pharmaceutical companies on the IDX for the period 2020 – 2024. The results of the analysis show that ROE does not have a significant effect on company value. Conversely, ROA and DER were found to contribute significantly to increased valuation. These findings offer strategic implications for the advancement of managerial theory and practice. For executive teams, the research results can be used as a reference for formulating policies to improve performance, particularly through asset – based profitability optimization. The indication that pharmaceutical entities during that period had not maximized the use of equity to boost profits points to the need for operational restructuring and increased capital efficiency. For further studies, it is recommended to avoid using ROE as a performance evaluation metric, given its ineffectiveness in describing the operational reality of the pharmaceutical sector on the IDX in the 2020 – 2024 period. Subsequent researchers may explore altervative indicators that are more appropriate for the pharmaceutical industry and the dynamics of the Indonesian capital market, such as R&D innovation ratios or sensitivity to fluctuations in raw material prices.